Environmental and Climate Changes and Cultural Response During Mid to Late Holocene at Babylon City- Iraq - Al-Tawash, Balsam; Ali, Maysoon; Al-Rawi, Yehya (Iraqi Journal of Science, 2023)
The study deals with palaeoecology and paleoclimates of Holocene sediments of historical Babylon area on palynological evidence which located at Euphrates river, (100) Km south of Baghdad. Links between environmental and socio- cultural changes are explored in archaeological and palaeoenvironmental data. The increased social and cultural developments as a response of enhanced aridity, driven by population accumulation in environments characterized by the presence of surface water resource. Three palaeoecological zones PZ1, PZ2, and PZ3 are deduced from the pollen diagram which reflect the climatic and ecologic changes throughout parts of the Holocene (5500-7500; 5500- 4000 and 4000-Present yr BP).Cereal grasses appear at the beginning of the PZ3 which indicate the flourishing of cultivation during the Palaeo-Babylonian and Meso-Babylonian periods (3950-2950 yr BP). Cereal grasses pollen (cultivated) distinguished from the wild grass pollen by their morphology and the pore shape and size. Social complexity and cultural development were largely driven by climatic and environmental changes that prevailed the area throughout parts of the Holocene, as a response to the increased aridity which has led to a great progress in the irrigation facilities and building dykes along the cultivated areas and social communities at the site, as well.